Impact of water hardness on oxytetracycline oral bioavailability in fed and fasted piglets - Decundo, Julieta María (2019)
Water hardness is a critical factor that affects oxytetracycline dissolution by chelation with cations. These interactions may lead to impaired dosing and consequently decrease absorption. Moreover, feed present in gastrointestinal tract may interact with antibiotic and alter pharmacokinetic parameters. In the present study, dissolution profiles of an oxytetracycline veterinary formulation were assessed in purified, soft and hard water. Furthermore, oxytetracycline absolute bioavailability, after oral administration of the drug dissolved in soft or hard water, was evaluated in fed and fasted piglets. A maximum dissolution of 86% and 80% was obtained in soft and hard water, respectively, while in purified water dissolution was complete. Results from in vivo study reconfirmed oxytetracycline´s very low oral bioavailability. The greatest values were attained when antibiotic was dissolved in soft water and in fasted animals. Statistically significant lower absolute bioavailability was achieved when hard water was used and/or animals were fed. Moreover, Cmax attained in all treatments was lower than MIC90 of most important swine pathogens. For these reasons, the oral use of OTC formulations, that have demonstrated low oral bioavailability, should be avoided to treat systemic diseases in pigs.